External irradiation effect on the growth and evolution of in-flame soot species - Wang, Cheng; Chan, Qing N.; Kook, Sanghoon; Hawkes, Evatt R.; Lee, Jeonghoon; Medwell, Paul R. (Carbon (New York), 2016)
External irradiation–soot species interaction is a subject that is of great interest due to its existing and future use in research diagnostics, nanomaterial synthesis and energy generation applications. An assessment of the influence of broadband radiation (ultraviolet to infrared wavelengths) on the evolution of soot species within a laminar ethylene-air flame is therefore performed to improve the fundamental understanding of the interaction process. Radiation at an average flux value of 120 kW/m2 is provided by a solid-state plasma light to the lower region of the flame. Soot samples are collected thermophoretically at flame positions that are close to and downstream from the irradiation location, to assess the effect of external irradiation on the evolution of in-flame soot species. The soot samples are imaged using normal-resolution and high-resolution transmission electron microscopes and the images obtained are analyzed. The application of an external irradiation source is found to increase the soot loading of the flame, and have a pronounced impact on the soot morphology, and influence the in-flame soot growth processes/mechanisms. The effects are also found to persist downstream from the irradiation location. The effects are mainly attributed to the coupling of the broadband irradiation with the soot precursors, for the configurations used.